Discovery and characterization of hydroxylysine in recombinant monoclonal antibodies. Issue 2 (17th February 2016) - Xie, Qing; Moore, Benjamin; Beardsley, Richard L.
ABSTRACT: Tryptic peptide mapping analysis of a Chinese hamster ovary (CHO)-expressed, recombinant IgG1 monoclonal antibody revealed a previously unreported +16 Da modification. Through a combination of MS n experiments, and preparation and analysis of known synthetic peptides, the possibility of a sequence variant (Ala to Ser) was ruled out and the presence of hydroxylysine was confirmed. Post-translational hydroxylation of lysine was found in a consensus sequence (XKG) known to be the site of modification in other proteins such as collagen, and was therefore presumed to result from the activity of the CHO homolog of the lysyl hydroxylase complex. Although this consensus sequence was present in several locations in the antibody sequence, only a single site on the heavy-chain Fab was found to be modified.